Implementation Of Educational Field Experience Program Activities In Schools With Motivation To Become Teacher In Pkk Program Students - Maiyandra, Vera; Elida, Elida (Jurnal Pendidikan Tata Boga dan Teknologi, 2023)
This research was motivated by the unpleasant experiences that were obtained when students carried out the Educational Field Experience Program (PPLK) activities such as students in schools who lacked respect and respect, duties and responsibilities that exceeded the obligations of PPLK students and the time for implementing PPLK that exceeded PPLK standards. Based on the pre-research, there was a decrease in students' desire and interest to become teachers. This study aims to analyze the relationship between the implementation of the Educational Field Experience Program and the motivation to become a teacher for PKK UNP study program students in 2015 and 2016. This type of research uses correlational quantitative. The population in this study were 192 students of the Family Welfare Education study program who had carried out PPLK. For sampling is Proportional Random sampling with the results of 66 people. Data collection was carried out by means of a questionnaire via Google From using a Likert Scale that has been tested for validity and reliability. Data were analyzed using descriptive correlation with the help of SPSS 17 and MS. Excel. The results showed that PPLK data descriptions were in the very high category. For motivation to become a teacher it is in the medium category. The correlation coefficient of PPLK implementation results with motivation to become a teacher in PKK UNP students with a value of r count > r table of 0.465 > 0.242 which means the correlation coefficient is positive. If it is interpreted into the Interpretation criteria, the correlation coefficient is the value r, then the correlation coefficient is at a moderate level because the value of r is in the range 0.400 – 0.599 with a significance value of 0.000 <0.05 which means that Ha is accepted and tcount > ttable, 30.140 > 1.670 It can be concluded that Ha is accepted and Ho is rejected at a significance level of 0.05 and it can be stated that there is a significant and positive relationship between PPLK implementation and the motivation to become a teacher in family welfare education students at Padang State University. Keywords: